The influence of bottom slope on sound signals transmission to receiver (Part A) submerged in water column - Salamon, Roman; Marszal, Jacek (International Journal of Electronics and Telecommunications, 2026)
Underwater acoustic communications (UAC) in shallow waters is an extremely challenging task. This becomes even more difficult when reliable communication with an object buried in seabed sediments is required. The work presented in two articles (Part A and Part B) is a continuation of the earlier work published in [1]. The articles present the simulation of an acoustic transmission channel, taking into account the bottom slope angle. The simulations utilized the impulse response method and the image source ray tracing technique. The articles present examples of data transmission in a shallow channel with a sloping bottom to a receiver submerged in the water column (Part A) and to a receiver buried in seabed sediments (Part B).